Home Births Among Ethnic Minority Communities in Bokeo Province, Lao People's Democratic Republic - Wungrath, Jukkrit; Sriwongphan, Rungrasami; Kapheak, Krissana; Ritthimon, Wanchalerm (Kesmas, 2024)
Home births among ethnic minorities in developing countries pose significant risks to maternal and neonatal health. In Lao PDR, the government has taken steps to manage home births through training traditional birth attendants, improving transportation, and establishing referral systems. However, high home birth rates in regions like Bokeo remain concerning. This review emphasized the need for more skilled birth attendants and better access to emergency obstetric care in rural, ethnic minority areas. This review used 40 articles published between 2000 and 2023 and highlighted gaps in research regarding healthcare access, cultural practices, socioeconomic barriers, and the role of traditional birth attendants. Suggested strategies included scholarships for midwifery training, expanding telemedicine, enhancing emergency transport, and partnering with NGOs for culturally sensitive outreach. Although each strategy has limitations, collectively, they can improve maternal and newborn health outcomes and reduce home birth risks. Addressing cultural beliefs and preferences is essential to encourage healthcare use, and community engagement plays a key role in promoting safer birth practices while respecting traditions. A holistic approach combining skilled healthcare, cultural sensitivity, and accessible services is crucial to improving maternal and newborn care in ethnic minority communities in Lao PDR.